2012
DOI: 10.1128/cvi.05563-11
|View full text |Cite
|
Sign up to set email alerts
|

Postvaccination Increase in Serotype 19A Pneumococcal Disease in Norway Is Driven by Expansion of Penicillin-Susceptible Strains of the ST199 Complex

Abstract: bSerotype replacement in invasive pneumococcal disease has been observed after widespread use of the 7-valent pneumococcal conjugate vaccine (PCV7). Replacement is dominated by penicillin-nonsusceptible serotype 19A in several countries. Antibiotic selection pressure has been proposed to interact with immunization, leading to rapid replacement. In Norway, where prescription of antibiotics is limited, post-PCV7 replacement by serotype 19A is dominated by penicillin-susceptible clones. Hence, serotype 19A replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…In addition, genotyping data showed that all genotype 19A clustered with the presumed founder ST847 which was the most prevalent throughout the study, suggesting a stable population. It has been speculated that serotype 19A replacement is driven by antibiotic selection pressure [10], although recent data from Norway have shown that replacement of serotype 19A, at least in the case of invasive disease, can occur in the absence of penicillin resistance [28]. In our study, high level penicillin resistance was not detected although a higher prevalence of intermediate resistance was observed in the last study CSS.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In addition, genotyping data showed that all genotype 19A clustered with the presumed founder ST847 which was the most prevalent throughout the study, suggesting a stable population. It has been speculated that serotype 19A replacement is driven by antibiotic selection pressure [10], although recent data from Norway have shown that replacement of serotype 19A, at least in the case of invasive disease, can occur in the absence of penicillin resistance [28]. In our study, high level penicillin resistance was not detected although a higher prevalence of intermediate resistance was observed in the last study CSS.…”
Section: Discussioncontrasting
confidence: 65%
“…A reassuring finding was that the overall prevalence of serotype 19A, an important cause of serotype replacement in many geographical areas [2], [3], [10], [13], [28], did not increase following vaccination, although there was an increase in the proportion of NVT isolates due to this serotype, and the prevalence of carriage with this serotype was no higher in wholly vaccinated than in partly vaccinated villages. In addition, genotyping data showed that all genotype 19A clustered with the presumed founder ST847 which was the most prevalent throughout the study, suggesting a stable population.…”
Section: Discussionmentioning
confidence: 99%
“…By design, the vaccine uptake differed between samples. The uptake of the "new vaccine" did not differ between 2008 and 2013: 40% (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for PCV7 versus 42% (38)(39)(40)(41)(42)(43)(44)(45)(46) for at least 1 immunization with PCV13. In 2013, children were reported to have suffered from upper respiratory tract infections in the past 3 months slightly more often than in 2008 [2013: 9% (7-12); 2008: Table 4).…”
Section: Comparing the Pcv13 Sample With The Prevaccination And Pcv7 mentioning
confidence: 83%
“…Worldwide, serotype 19A has been reported as a main replacing serotype after PCV7 introduction, 13,15 and ST199 was the main replacing clone in Norway. 41 As no carriage data from just before the switch to PCV13 are available, we do not know whether 19A carriage continued to increase after 2008 and started to decrease after switching to PCV13, as seen for IPD, 19 or whether the 19A prevalence has remained stable. Several studies suggest that the effectiveness of PCV13 for serotype 3 is lower compared with other serotypes.…”
Section: Discussionmentioning
confidence: 95%
“…The potential genetic causes of the selec- (14). Contrary to the experience of the United States and several other countries, Norway, a country with a prevailing strict antibiotic prescription practice, experienced a postvaccination increase of serotype 19A driven by the expansion of CC199 isolates (15). Thus, it appears that antibiotic pressure may be the most important, but not the only, factor in the successful establishment of serotype 19A ST320 in many parts of the world.…”
mentioning
confidence: 85%